Transformasi Pembelajaran Akuntansi Melalui Pengembangan E-LKPD Berbasis Google Sites pada Elemen Akuntansi Lembaga/Instansi Pemerintah di SMKN 1 Duduksampeyan - Putri Aisyah; Moh. Danang Bahtiar (Mataram University, 2026)
Technological developments in the era of Industry 4.0 and Society 5.0 demand more interactive instructional materials, including for the Government Institution Accounting course in Vocational High Schools (SMK). Learning on village financial administration material at SMKN 1 Duduksampeyan still largely relies on lectures and printed student worksheets (LKPD), resulting in passive students who struggle to understand this complex, procedural, and regulation-based material. This study aims to produce a Google Sites-based Electronic Student Worksheet (E-LKPD) on village financial administration material and to determine its feasibility and student response toward the developed product. This study employed a Research and Development (R&D) approach with the 4D model, encompassing the define, design, develop, and disseminate stages, limited to the develop stage. Research subjects consisted of two material experts, two language experts, two media experts, and 30 twelfth-grade Accounting students at SMKN 1 Duduksampeyan. Data were collected through interviews, expert validation questionnaires, and student response questionnaires, then analyzed descriptively and quantitatively using Likert and Guttman scales. The results showed that material expert validation obtained a percentage of 89%, language experts 89%, and media experts 91%, with an overall average validation score of 90%, categorized as